ANALYSIS OF FACTORS THAT AFFECT WORK MOTIVATION OF AGRICULTURAL EXTENSION AGENTS ON SAGO COMMODITY IN MERANTI ISLANDS REGENCY - Fariz al azmi; Rosnita '; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: (1) Know implementation of extension and work motivational factors that influence agricultural extension on sago commodity in Meranti Islands Regency; (2) Analyze the work motivation level of agricultural extension agents work motivation who looked from internal and external factors and analyze how far the influence of each factors to agricultural extension agents work motivation on sago commodity in Meranti Island Regency. This research was counducted in Meranti Islands Regency. The research method used purposive samling with looked at the extension agents by its region and according to area and sago plantation in Meranti Island Regency. 30 extension agents taken as respondents. The research used validity and reliability analysis. Analysis of data for the first purpose using the Scale Likert summated Rating (SLR), while for the second purpose used multiple regression analysis. Research results showed: (1) The execution of counseling Meranti island Regency is already well underway. (2) extension officers work Motivation on commodity sago Meranti Island Regency are on the category “ Medium” and the factors that affect the motivation of extension officers work on commodity sago Meranti Island Regency personal maturity factor, namely, the desire to work, fatigue and boredom, good supervision, compensation, job satisfaction, and regulations has no effect in real and influential in the real work environment. Kata Kunci : Motivation,working,extension agent